Demands of the Employers for Foreign Language Skills in Job Advertisements in Three Baltic Countries - Kiškytė, Milda (Socialiniai tyrimai, 2023)
Recent studies showed that language knowledge has, increasingly, become a value-add attribute that helps businesses to implement and satisfy their corporate goals in the globalized world as its services are highly demanded by employers in parallel to so-called hard skills in job advertisements. The paper presents a quantitative content-based analysis of foreign language knowledge requirements listed in job advertisements. The study results are based on data assessment from online job websites. The scope of the study was five industries-information technology, finance and accounting, organization and management, technical engineering, and customer service in three Baltic States - Lithuania, Latvia and Estonia. The dataset consists of one thousand four hundred forty-two (N=1442) job advertisements written in English, published on the job portal, and examined from September 2021 to September 2022. The study results revealed that foreign language communication has become an obligatory attribute of the examined industries in the Baltic States and an indispensable characteristic of any working position. Labour market in Lithuania, Latvia and Estonia seeks a candidate with highly fluent foreign language skills, advanced expression of thoughts and communication, able efficiently to present thoughts, ideas or comments and communicate correctly.
Keywords: language knowledge; job advertisement; employability; business industry; the Baltic States